Formulasi Sediaan Serum Anti Aging dengan Kombinasi dari Ekstrak Buah Tomat (Lycopersicum esculentum L.) dan Ekstrak Kulit Buah Semangka (Citrullus lanatus Thunb.) - Rima Apria Purwanti; Yunahara Farida; Shelly Taurhesia (Faculty of Pharmacy, Universitas Muslim Indonesia, 2022)
Aging is a problem for everyone, especially those who have entered middle age and above. Aging can be caused by various factors, namely factors that come from within the body and from outside the body. One of the extrinsic factors were sun exposure, temperature / humidity and free radicals. Skin aging is mostly caused by free radicals, one of which is sunlight radiation. This study aims to produce a serum preparation that functions as an antioxidant with a combination of tomato extract and watermelon rind. The antioxidant activity of tomato extract, watermelon rind extract and combination extract was carried out using the DPPH method, then the anti aging serum was formulated using hydroxy ethyl cellulose, glycerin, DMDM hydantoin, ethoxy diglycol and aqua DM. Evaluation of serum preparations includes physical evaluation (organoleptic examination, dispersibility, homogeneity, viscosity, irritation test), chemistry (pH), and microbiology. Data were analyzed using one way Anova, the results differed significantly when the p-value was less than 0.05 (p <0.05). The results showed that the combination extract had a better IC50 value of 59.19 ppm, tomato extract 69.89 ppm, watermelon rind extract 79.29 ppm. Combined serum preparation at F1 (T: S / 1: 1) IC50 value was 97.37 ppm, F2 (T: S / 1: 2) 80.70 ppm, F3 (T: S / 2: 1) 69.81 ppm so it is included in the category of strong antioxidants.